2006
DOI: 10.1159/000093284
|View full text |Cite
|
Sign up to set email alerts
|

Allergic and Anaphylactic Response to Sesame Seeds in Mice: Identification of Ses i 3 and Basic Subunit of 11s Globulins as Allergens

Abstract: Background: Allergy to sesame seeds is an emerging food allergy of a serious nature due to a high risk of systemic anaphylaxis. Although a mouse model to study sesame anaphylaxis is desirable, currently it is not available. Here, using a transdermal exposure model system, we tested the hypothesis that sesame seed elicits IL-4-associated IgE antibody response with consequent clinical sensitization in mice. Methods: Groups of BALB/c mice were exposed to sesame seed extract or saline or a control food (vanilla be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…A few recent studies including ours demonstrate that transdermal exposure to allergenic food proteins such as hazelnut, ovalbumin, cashew nut and sesame seed can result in clinically significant sensitization [19,22,23,24]. These data demonstrate, for the first time, that just two transdermal exposures during the allergen withdrawal period can trigger a vigorous booster immune response with consequent clinical reactivity upon oral challenge.…”
Section: Discussionsupporting
confidence: 53%
“…A few recent studies including ours demonstrate that transdermal exposure to allergenic food proteins such as hazelnut, ovalbumin, cashew nut and sesame seed can result in clinically significant sensitization [19,22,23,24]. These data demonstrate, for the first time, that just two transdermal exposures during the allergen withdrawal period can trigger a vigorous booster immune response with consequent clinical reactivity upon oral challenge.…”
Section: Discussionsupporting
confidence: 53%
“…However, few recent studies, including ours, have shown that transdermal exposure to other allergenic food proteins, e.g. ovalbumin, hazelnut and sesame seed, can result in both immune activation and clinical sensitization for immediate hypersensitivity reaction including systemic anaphylaxis [18, 19, 22]. Strid et al [23 ]demonstrated a delayed hypersensitivity response to peanut via skin exposure in the ear using the tape-stripping method.…”
Section: Discussionmentioning
confidence: 96%
“…We chose the BALB/c strain of mice to develop a cashew nut allergy model because: (i) this strain has earlier been used in allergy studies by many in the field including us; however, whether they develop allergic responses to cashew nut was unknown [18,19,20,21], and (ii) many gene knockout mice are available on BALB/c genetic background, and therefore it will be valuable for further mechanistic studies on cashew nut allergy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most food allergies typically start in infancy and tend to be outgrown before adulthood, some food allergies such as tree nut allergies are considered to last for a lifetime as chances of outgrowing such sensitizations are minimal [1]. Furthermore, peanuts, tree nuts (such as hazelnuts and walnuts) and sesame seeds are the major food types that often cause systemic anaphylaxis with fatal or near-fatal consequences [1, 2, 5, 6]. Thus, tree nut allergy is a clinically significant and very serious immune-mediated disorder that remains incompletely understood at present.…”
Section: Introductionmentioning
confidence: 99%